Planning, operation, and control of bus transport systems: A literature review. (July 2015) - Ibarra-Rojas, O.J.; Delgado, F.; Giesen, R.; Muñoz, J.C.
Highlights: We review the literature on planning and network design of urban transport focusing on bus service. We review the literature on operation, and control of urban transport focusing on bus service. We provide a comprehensive classification of the studies presented in this field. Abstract: The efficiency of a transport system depends on several elements, such as available technology, governmental policies, the planning process, and control strategies. Indeed, the interaction between these elements is quite complex, leading to intractable decision making problems. The planning process and real-time control strategies have been widely studied in recent years, and there are several practical implementations with promising results. In this paper, we review the literature on Transit Network Planning problems and real-time control strategies suitable to bus transport systems. Our goal is to present a comprehensive review, emphasizing recent studies as well as works not addressed in previous reviews.